2021
DOI: 10.1186/s13046-021-02163-7
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific peptidase 37: an important cog in the oncogenic machinery of cancerous cells

Abstract: Protein ubiquitination is one of the most crucial posttranslational modifications responsible for regulating the stability and activity of proteins involved in homeostatic cellular function. Inconsistencies in the ubiquitination process may lead to tumorigenesis. Ubiquitin-specific peptidases are attractive therapeutic targets in different cancers and are being evaluated for clinical development. Ubiquitin-specific peptidase 37 (USP37) is one of the least studied members of the USP family. USP37 controls numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…Different USPs have specific substrate proteins; therefore, they can regulate different signaling pathways ( Ye et al, 2009 ). USPs can stabilize various oncoproteins or alter their cellular localization by deubiquitination, which can cause the development and progression of cancer ( Chauhan et al, 2021 ). Numerous studies have shown that targeting USPs might be a promising therapeutic approach for cancer treatment ( Dai et al, 2020 ; Du et al, 2021 ; Li et al, 2020 ; Ma et al, 2019 ; Nininahazwe et al, 2021 ; Zhu et al, 2020 ).…”
Section: Survey Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Different USPs have specific substrate proteins; therefore, they can regulate different signaling pathways ( Ye et al, 2009 ). USPs can stabilize various oncoproteins or alter their cellular localization by deubiquitination, which can cause the development and progression of cancer ( Chauhan et al, 2021 ). Numerous studies have shown that targeting USPs might be a promising therapeutic approach for cancer treatment ( Dai et al, 2020 ; Du et al, 2021 ; Li et al, 2020 ; Ma et al, 2019 ; Nininahazwe et al, 2021 ; Zhu et al, 2020 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…1 , ubiquitin can covalently conjugate to the substrate proteins by three different enzymes, including E1, E2, and E3, during ubiquitination ( Clague, Heride & Urbé, 2015 ). In eukaryotes, the ubiquitin-proteasome system, which is mainly composed of ubiquitin molecules, ubiquitylating enzymes, and 26S proteasomes, is an important pathway for the degradation of damaged or misfolded proteins ( Chauhan et al, 2021 ; Svikle et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a reversible process and a key post‐translational modification, which is counter‐regulated by ubiquitinating enzymes and deubiquitinases 6,7 . Ubiquitination regulates protein stability and activity and is involved in homeostatic cellular functions 8 . By labeling proteins degraded by the proteasome, ubiquitination has always been considered a key determinant of protein fate 9 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Ubiquitination regulates protein stability and activity and is involved in homeostatic cellular functions. 8 By labeling proteins degraded by the proteasome, ubiquitination has always been considered a key determinant of protein fate. 9 Deubiquitinases drive the cleavage of ubiquitin from substrates, which control the stability of most cellular proteins.…”
mentioning
confidence: 99%
“…Cohesin dissociation from chromatin requires the activity of WAPL (Wings Apart-like Protein 1) which interacts directly with RAD21 and STAG1/2 [ 8 , 9 ]. Recently, it has been shown that WAPL is deubiquitinated by USP37 (Ubiquitin-specific peptidase 37) during mitosis, thereby regulating chromosomal segregation, cohesion and mitotic progression [ 10 , 11 ]. Finally, once chromosomes are correctly bioriented on the mitotic spindle at anaphase, cohesin is completely removed from chromosomes by the endopeptidase ESPL1 (Extra spindle pole bodies-like 1)/SEPARASE protein that cleaves RAD21 [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%